Digitality and immaterial culture: What did Viking women think?. (25th November 2008) - Thomas, Maureen
The digital interactive audiovisual work, RuneCast, designed for installation-projection to supplement artefacts on display, suggests how digital media can be used to extend the museum visit. The oral composition techniques of the Viking age are adapted for computational narrativity, and authentic sung and spoken verse is interpreted through associative, kaleidoscopically reconfiguring, layered video and animation – evoking rather than documenting the ethos of the period it illuminates. Like its inspiration, the Eddaic poem, Voluspaa (Songs of the Seeress), RuneCast's voices are female, not only invoking the world of men, but also expressing and communicating that of Viking women.